Systematic Literature Review (SLR) : Filsafat dan Ilmu Pengetahuan - Ahmad Gozi; Nida Adenia Rahma; Agung Winarno (Jurnal bintang manajemen, 2025)
This article discusses philosophy and science which are human efforts in understanding a concept and method of a science. The development of science will not be far from a person's way of thinking through philosophy that is never satisfied with the results found. With the way science develops, there are new findings to improve human knowledge. This article aims to find out more about the role of philosophy in science which is carried out with a theoretical perspective related to the nature of science which includes ontology, epistemology, and axiology. This type of article uses the SLR (Systematic Literature Review) method. The sources obtained come from publish or perish 8.